Intelligent networks principles and applications - Anderson, J. R. (John R.) (Institution of Engineering and Technology, 2002)
The purpose of this book is to give some practical insight into how public telecommunications networks have advanced from the old days of offering just simple telephony services to becoming today's 'intelligent' networks. Telephone companies now operate in an intensely competitive environment, and so they have to constantly struggle to find more ways to encourage customers to make ever more use of the installed network equipment. Network operators are therefore constantly looking for new services that will make the telephone system more attractive, easier to use and perhaps even more indispensable for its users. The overall goal is of course to increase the revenue-producing ability of the existing phone systems. The aim of the 'intelligent network' (IN) has always been to help the telephone companies achieve just this, but in a rigorously standard manner, so that network equipment from different suppliers can work together. IN seeks to provide the internal network rearrangements that give the agility and flexibility needed to bring almost any new services into life very quickly.